1986
DOI: 10.1128/mcb.6.4.1179
|View full text |Cite
|
Sign up to set email alerts
|

In vivo levels of diadenosine tetraphosphate and adenosine tetraphospho-guanosine in Physarum polycephalum during the cell cycle and oxidative stress.

Abstract: Cellular levels of diadenosine tetraphosphate (Ap4A) and adenosine tetraphospho-guanosine (Ap4G) were specifically measured during the cell cycle of Physarum polycephalum by a high-pressure liquid chromatographic method. Ap4A was also measured indirectly by a coupled phosphodiesterase-luciferase assay. No cell cycle-specific changes in either Ap4A or Ap4G were detected in experiments involving different methods of assay, different strains of P. polycephalum, or different methods of fixation of macroplasmodia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…The reasons for this discrepancy are not quite clear, but it must be stressed that our determinations of ATP and Ap4A, for instance, are in good agreement with those reported in references 3 and 21. Our conclusions are further supported by the recent work of Garrison et al (11), who showed that no variation in the Ap4X level could be observed in the autosynchronous growth of Physarum polycephalum, in contrast to an earlier publication by Grummt and co-workers (31) According to all these data, as well as findings presented elsewhere (3, 9, 11), the concept of Ap4A as a trigger of the proliferative state of eucaryotic cells has to be seriously reexamined. We cannot, however, completely rule out participation of Ap4A in the tuning of the DNA synthesizing machinery, on the basis of in vitro experiments showing, first, that an Ap4A-binding activity is found tightly associated to DNA polymerase a (5,13,20,24,29,37).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The reasons for this discrepancy are not quite clear, but it must be stressed that our determinations of ATP and Ap4A, for instance, are in good agreement with those reported in references 3 and 21. Our conclusions are further supported by the recent work of Garrison et al (11), who showed that no variation in the Ap4X level could be observed in the autosynchronous growth of Physarum polycephalum, in contrast to an earlier publication by Grummt and co-workers (31) According to all these data, as well as findings presented elsewhere (3, 9, 11), the concept of Ap4A as a trigger of the proliferative state of eucaryotic cells has to be seriously reexamined. We cannot, however, completely rule out participation of Ap4A in the tuning of the DNA synthesizing machinery, on the basis of in vitro experiments showing, first, that an Ap4A-binding activity is found tightly associated to DNA polymerase a (5,13,20,24,29,37).…”
Section: Discussionsupporting
confidence: 82%
“…It could be argued that our determinations, performed by the coupled luciferase-phosphodiesterase assay (18), in fact detect all dinucleoside polyphosphates (of general structure Ap,X, where X is any nucleoside and n is -4). It must be stressed, however, that Ap4A is the major component that contributes to the bioluminescence signal in cellular extracts, as shown by high-performance liquid chromatography (2,3,7,11), so that the values measured for Ap4X most likely reflect the level of Ap4A with a good accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dinucleoside polyphosphates (7). The dinucleoside polyphosphate Ap 4 A 1 is induced upon oxidative stress and heat shock both in prokaryotes and eukaryotes (8,9), and the Nudix enzyme subsequently degrades this signaling component to restore the intracellular balance. Experimental data indicate that an increased concentration of Ap 4 A is a signal for cell division in Escherichia coli (10).…”
mentioning
confidence: 99%
“…However, Bambara et al (5) have presented arguments against this putative function of Ap4A. The constancy of Ap4A during traverse of the cell cycle in Physarum polycephalum (16), E. coli (40), and cultured mammalian cells (35,38) also argues against the hypothesis that Ap4A is a positive regulator of DNA synthesis.…”
mentioning
confidence: 96%